2020
DOI: 10.1016/s2352-4642(20)30239-x
|View full text |Cite
|
Sign up to set email alerts
|

A machine-learning algorithm for neonatal seizure recognition: a multicentre, randomised, controlled trial

Abstract: Background Despite the availability of continuous conventional electroencephalography (cEEG), accurate diagnosis of neonatal seizures is challenging in clinical practice. Algorithms for decision support in the recognition of neonatal seizures could improve detection. We aimed to assess the diagnostic accuracy of an automated seizure detection algorithm called Algorithm for Neonatal Seizure Recognition (ANSeR). Methods This multicentre, randomised, two-arm, parallel, controlled trial was done in eight neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 40 publications
0
95
0
Order By: Relevance
“…of HIE in the primary study 65 40 59 62 Total mild HIE in the primary study 29 24 36 30 No. in the current study (mild HIE and EEG recording <6 hours of life) 9 16 19 14 Definition of mild HIE ≥1 abnormal finding on modified Sarnat Score at 24 hours of life but not meeting criteria for moderate or severe HIE Worst grade of encephalopathy in the first 24 hours using modified Sarnat Score but not meeting criteria for TH Worst grade of encephalopathy in the first 24 hours using modified Sarnat Score but not meeting criteria for TH 1 or more abnormal neurological finding on modified Sarnat Score at 1 hour of life but not meeting criteria for TH Exclusion from pooling (1) Infants who received TH ( n = 1) (1) Infants who received TH ( n = 4) (2) Other diagnosis than mild HIE (1) Infants who received TH ( n = 2) Main publications from cohorts to date Murray et al 57 Murray et al 58 Murray et al 59 Murray et al 30 Murray et al 23 Murray et al 15 Walsh et al 60 Walsh et al 61 Walsh et al 62 Walsh et al 63 Looney et al 64 O’Sullivan et al 65 Rennie et al 66 O’Sullivan et al 67 Finder et al 16 Pavel et al 68 TH therapeutic hypothermia, HIE hypoxic–ischaemic encephalopathy, GA gestational age, CPR cardiopulmonary resuscitation, PA perinatal asphyxia. a Exclusion from primary studies: infants <36 + 0 weeks’ gestation; known genetic disorders and/or inborn errors of metabolism; confirmed sepsis (positive blood or CSF cultures).…”
Section: Methodsmentioning
confidence: 99%
“…of HIE in the primary study 65 40 59 62 Total mild HIE in the primary study 29 24 36 30 No. in the current study (mild HIE and EEG recording <6 hours of life) 9 16 19 14 Definition of mild HIE ≥1 abnormal finding on modified Sarnat Score at 24 hours of life but not meeting criteria for moderate or severe HIE Worst grade of encephalopathy in the first 24 hours using modified Sarnat Score but not meeting criteria for TH Worst grade of encephalopathy in the first 24 hours using modified Sarnat Score but not meeting criteria for TH 1 or more abnormal neurological finding on modified Sarnat Score at 1 hour of life but not meeting criteria for TH Exclusion from pooling (1) Infants who received TH ( n = 1) (1) Infants who received TH ( n = 4) (2) Other diagnosis than mild HIE (1) Infants who received TH ( n = 2) Main publications from cohorts to date Murray et al 57 Murray et al 58 Murray et al 59 Murray et al 30 Murray et al 23 Murray et al 15 Walsh et al 60 Walsh et al 61 Walsh et al 62 Walsh et al 63 Looney et al 64 O’Sullivan et al 65 Rennie et al 66 O’Sullivan et al 67 Finder et al 16 Pavel et al 68 TH therapeutic hypothermia, HIE hypoxic–ischaemic encephalopathy, GA gestational age, CPR cardiopulmonary resuscitation, PA perinatal asphyxia. a Exclusion from primary studies: infants <36 + 0 weeks’ gestation; known genetic disorders and/or inborn errors of metabolism; confirmed sepsis (positive blood or CSF cultures).…”
Section: Methodsmentioning
confidence: 99%
“…The challenge of eliminating the duration from the neonatal seizure definition is that it hinders our ability to directly apply the current literature to bedside clinical care; recent studies have consistently defined an EEG seizure as at least 10 seconds in duration. [6][7][8][9][10][11] We do not know how the published data apply to seizures that last less than 10 seconds. This change will also introduce potentially significant variability to future studies.…”
Section: Definition Of Eeg Seizures Is Proposedmentioning
confidence: 99%
“…Much effort was made to develop automated seizure detection. When tested, all algorithms showed clinically relevant detection rates ( 38 ). Doyle et al ( 39 ) and Malarvilli and Mesbah ( 40 ) used heart rate variability to detect seizures.…”
Section: The Role Of Precision Medicine For “Brain Oriented Care”mentioning
confidence: 99%
“…Recently, an ML algorithm for neonatal seizure recognition, ANSeR, was investigated in a randomised controlled trial and was found to be safe and able to detect neonatal seizures. However, it did not yet improve the identification of individual neonates with seizures ( 38 ).…”
Section: The Use Of Eeg/aeeg For Precision Medicinementioning
confidence: 99%